Daya Analgetik Dekokta Daun Meniran (Phyllanthus niruri L) Pada Mencit Dengan Induksi Asam Asetat - Hastuti, Siwi (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2024)
Pain occurs with many disease processes or in conjunction with some diagnostic tests or treatments. Pain bothers and troubles more people than any other disease. Research on the meniran plant (Phyllanthus niruri L) for analgesic activity has been reported, but on dekokta preparations it has never been reported. The aim of this research is to analyze the analgesic effect of meniran herbs dekokta on mice using the chemical stimulation method of 1% acetic acid. The method for extracting the test preparations uses the method decoctation with dekokta levels made of 15%, 30% and 60%. The positive control used was paracetamol 65 mg/kgBW. The mice used were Swiss strain male mice. Test the pharmacological activity by making five test groups, namely negative control test, positive control test , 15% preparation test, 30% preparation test and 60% preparation test. Observations were in the form of the number of mice writhing which was then used to calculate the percentage of analgesic power. The data analysis technique used the ANOVA method with a confidence level of 95%. Meniran herbs decoct has analgesic activity in mice respectively at doses of 15%, 30% and 60% were (27.96 ± 0.67) %, (34.74 ± 1.28) % and (38.55 ± 0.66) % while on paracetamol 65 mg/kgBW is (42.79±0.94)%. The statistical test results showed that there was a significant difference in the percentage of analgesic power between the test preparation treatments. Dekokta meniran herbs have the potential to be developed as a natural medicine for analgesics.